2009
DOI: 10.4067/s0717-95022009000100030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol Extract of Whole Plant of Trichosanthes cucumerina var. cucumerina L. on Gonadotropins, Ovarian Follicular Kinetics and Estrous Cycle for Screening of Antifertility Activity in Albino Rats

Abstract: Ethanol extract of whole plant of Trichosanthes cucumerina L. var. cucumerina was evaluated for antiovulatory activity in adult rats. The ethanol extract at the doses 200 and 400mg/kg body weight (orally) affected the normal estrous cycle showing a significant increase in estrus and metestrus phases and decrease in diestrus and proestrus phases. The extract also significantly reduced the number of healthy follicles (Class I-Class VI) and corpora lutea and increased the number of regressing follicles (Stage IA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…During the initial development, the ovarian follicles cells produce estrogen, and during the latter stage under the influence of LH, they produce progesterone [23,24]. Since the maturation of follicles has been affected by Neem seed oil and its Fraction IV and Fraction V. In the all above three treatment groups, the number of follicles reduces drastically which reflects inhibitory function of neem seed oil and its Fraction IV and V. Similarly, the increased level of serum cholesterol may show the antiestrogenic nature of plant material because cholesterol is an important precursor in synthesis of steroid hormones [25][26][27][28]. The specific function of cholesterol in the ovary is to act as precursor molecule for synthesis of estrogen [29] so the increased level is thus due to non-utilization of cholesterol due to inhibitory ovary function so it is confirmed that Neem seed oil alone and its Fraction IV and V may affect the intraovarian estrogen level either by inhibiting the ovarian cell function or by inhibiting follicle-stimulating hormone and LH secretion through hypothalamus-hypophysis axis, and impaired estrogen synthesis has been achieved resulting infertility.…”
Section: Vyas and Purohitmentioning
confidence: 99%
“…During the initial development, the ovarian follicles cells produce estrogen, and during the latter stage under the influence of LH, they produce progesterone [23,24]. Since the maturation of follicles has been affected by Neem seed oil and its Fraction IV and Fraction V. In the all above three treatment groups, the number of follicles reduces drastically which reflects inhibitory function of neem seed oil and its Fraction IV and V. Similarly, the increased level of serum cholesterol may show the antiestrogenic nature of plant material because cholesterol is an important precursor in synthesis of steroid hormones [25][26][27][28]. The specific function of cholesterol in the ovary is to act as precursor molecule for synthesis of estrogen [29] so the increased level is thus due to non-utilization of cholesterol due to inhibitory ovary function so it is confirmed that Neem seed oil alone and its Fraction IV and V may affect the intraovarian estrogen level either by inhibiting the ovarian cell function or by inhibiting follicle-stimulating hormone and LH secretion through hypothalamus-hypophysis axis, and impaired estrogen synthesis has been achieved resulting infertility.…”
Section: Vyas and Purohitmentioning
confidence: 99%
“…Different parts of this plant are used in traditional medicines; for example, in the treatment of inflammatory conditions, liver disorders and gastrointestinal problems. The plant is also known to affect female reproduction . Extracts of the whole plant disrupted ovulation in female rats .…”
Section: Plant Extracts With Effects On Ovarian Function Of Female Romentioning
confidence: 99%
“…The plant is also known to affect female reproduction . Extracts of the whole plant disrupted ovulation in female rats . Oral administration of an ethanol extract (200 and 400 mg kg −1 body weight) for 30 days disrupted the oestrous cycle, leading to significant increases in the oestrous and metoestrous phases.…”
Section: Plant Extracts With Effects On Ovarian Function Of Female Romentioning
confidence: 99%
See 1 more Smart Citation
“…are used as laxative, purgative, antipyretic, alexiteric and antiulcer agent (Kirtikar and Basu, 1935). Scientific evidences regarding antidiabetic (Kirana and Srinivasan, 2008), hepatoprotective (Kumar et al, 2009), anti-inflammatory (Kolte et al, 1996), antifertility (Kage et al, 2009), antioxidant (Adebooye, 2008), antibacterial (Hariti and Rathee, 1995), antifungal (Harit and Rathee, 1996) and antiviral (McGrath et al, 1992) activities of the plant were reported. The fruits contain ascorbic acid, lycopene, phenols, flavonoids, alkaloids, tannins and saponins (Adebooye, 2008;Edeoga et al, 2010).…”
Section: Introductionmentioning
confidence: 99%